On the nonlinear dynamics of viscoelastic graphene sheets conveying nanoflow: Parametric excitation analysis. Issue 3 (4th March 2022) - Shariati, Ali; Ebrahimi, Farzad; Hosseini, S. Hamed S.; Toghroli, Ali; Bayrami, S. Sedighi
Abstract: The present article aims to clarify the effect of the nanoflow on the nonlinear dynamic instability of graphene sheets under parametric excitation. To achieve this aim, the graphene layer is added to a visco-Pasternak foundation then, the resulting nanostructure is subjected to the nanoflow and a parametric axial force, simultaneously. The nonlocal elasticity and the nonlinear von Karman theories and Hamilton's principle are combined in this article, which lead to the governing equation of motion. A class of nonlinear Mathieu–Hill equation is established to determine the bifurcations and the regions of the nonlinear dynamic instability. The main conclusion to be drawn is that nanoflow directly influences the amplitude response of the system. This investigation contains analysis of how the nanoflow affects the nonlinear instability of nanostructures including the graphene sheets which can be provided useful information for the next investigations in field of nano electromechanical system.